Advanced Machining and Manufacturing Processes - Kumar, Kaushik; Zindani, Divya; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book covers the various advanced manufacturing processes employed by manufacturing industries to improve their productivity in terms of socio-economic development. The authors present automated conventional and non-conventional machining techniques as well as virtual machining principles and techniques. Material removal by mechanical, chemical, thermal and electrochemical processes are described in detail. A glossary of key concepts is attached at end of the book. .
Automated Conventional Machining Techniques -- Non Conventional Machining Techniques -- Virtual Manufacturing.
Keywords: Manufactures; Machinery; Electrochemistry; Machines, Tools, Processes; Machinery and Machine Elements; Electrochemistry